#TITLE_ALTERNATIVE# - ROSYIDAH NIM : 10714074, AFIFATUR
Currently, there is an analgesic tablet which consists of paracetamol, aspirin, and caffeine combination. Compendia’s method to determine the contents of the active compounds is HPLC. This study aimed to obtain an alternative analysis method of those combination tablet using spectrofluorometer. This study was performed by dissolving all standard of components in a few ethanol, then it was added with aquadest until the proportion of (1:10). The solution then measured with spectrofluorometer. The emission spectrum of each substance was optimized respectively. The result of each spesific emission which was separated from one another was shown at 723-725 nm for paracetamol, 798-800 for aspirin, and 758-760 for caffeine. Validation test result of linearity that is represented by (r) of the substances were: 0.9989; 0.9998; and 0.9996. Next, this method was already tested and proven to fulfill the criterion of acceptance of all validation parameters. The limit of quantification (LOQ) was 28.986 ppm for paracetamol, 7.024 ppm for aspirin, and 2.773 ppm for caffeine, respectively. The validated method was used to determine the contain of tablet which was found in the market. The tablet which were tested showed that it matched with the content requirement. This method showed the a hundred portion smaller in sensitivity compared to HPLC as counterpart based on the literature. On the other hand it was more selective than spectrophotometry UV reported on a reference. Technically, this method was easier, because it had simpler preparation of the sample and it didn’t spend many solvents and column system. Therefore, it can be considered to use this spectrofluorometry method as an alternative to analyze paracetamol, aspirin, and caffeine in the combination tablet.